Evaluation of virulence genes in Yersinia enterocolitica strains using SYBR Green real-time PCR. (August 2017) - Peruzy, Maria Francesca; Murru, Nicoletta; Perugini, Anna Giannina; Capuano, Federico; Delibato, Elisabetta; Mercogliano, Raffaelina; Korkeala, Hannu; Proroga, Yolande Therese Rose
Abstract: Yersinia enterocolitica comprises six biotypes 1A, 1B, 2, 3, 4, and 5. The virulence of the strains belonging to biotypes 1B and 2–5 depends on the presence of both chromosomal and plasmid-borne genes. Strains belonging to biotype 1A do not carry the virulence plasmid pYV. However, they carry other virulence genes, such as ystB and hreP . The aim of this study was to investigate the distribution of yadA, virF, inv, ystA, ystB, myfA, hreP and ymoA virulence genes in Y. enterocolitica strains in order to select the target genes that could be used for the development of a probe-specific real-time PCR to determine the presence of Y. enterocolitica in food samples. A total of 161 Y. enterocolitica strains isolated in eight countries and grouped into biotypes 1A, 2 (serotypes O3, O5 and O9), 3 (serotypes O3 and O9) and 4 (serotype O3) were examined for virulence genes. The most common virulence-associated gene in pathogenic Y. enterocolitica proved to be ystA, which can therefore be considered the best target gene to be amplified in order to evaluate the presence of pathogenic biotypes. By contrast, to identify Y. enterocolitica 1A strains, ystB, which codes for the enterotoxin YstB, can be proposed. This has been found in all non-pathogenic biotypes studied, but never in pathogenic biotypes. Highlights: The presence of virulence genes in strains of Y. enterocolitica was studied. Differences between strains of Y. enterocolitica from eight countries was evaluated. ystA can be considered the best target gene to be amplified. To identify B1A strains ystB gene, coding for the enterotoxin YstB, can be used.